Nexus of environmental management accounting, and carbon emission management on environmental, social, and governance performance: evidence from symmetrical and asymmetrical approach - Liu Xia; Nazneen Fatema; Md. Mominur Rahman; Arman Hossain (Humanities & Social Sciences Communications)
Abstract In the face of increasing global pressure for sustainable business practices, the adoption of Environmental Management Accounting (EMA) has emerged as a critical tool for enhancing Environmental Social Governance (ESG) performance. However, there remains a research gap in understanding the specific impact of EMA practices on ESG outcomes, particularly in the context of Bangladesh’s manufacturing sector. This study aims to fill this gap by examining the direct and moderating effects of EMA practices—namely Eco-Efficiency Improvement (EEI), Environmental Cost Tracking (ECT), Life Cycle Assessment Integration (LCAI), and Environmental Reporting Transparency (ERT)—on ESG performance, as well as the role of Carbon Emission Management (CEM) in influencing these relationships. Using a sample of 238 manufacturing firms, the study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) for measurement and structural modeling, along with fsQCA to assess necessity conditions and perform configurational analysis. The findings reveal that EMA practices significantly impact ESG performance, with direct positive effects from EEI, ECT, LCAI, and ERT. CEM also has a direct positive effect on ESG performance and moderates the relationship between EMA practices and ESG outcomes. Additionally, fsQCA analysis identifies synergistic effects of EMA and CEM, revealing configurations that contribute to high ESG performance. The study highlights the importance of integrating EMA practices into corporate strategies for enhancing ESG outcomes. For policymakers, the results provide valuable insights into designing regulations that encourage firms to adopt and strengthen EMA practices, ultimately promoting sustainable business practices. The study suggests that policymakers should focus on creating frameworks that incentivize the adoption of comprehensive EMA strategies and support the integration of CEM, facilitating the transition to more sustainable and responsible business practices within the manufacturing sector.